2006
DOI: 10.1038/sj.ki.5000023
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide linkage scan for genes controlling variation in urinary albumin excretion in type II diabetes

Abstract: The main hallmark of diabetic nephropathy is elevation in urinary albumin excretion. We performed a genome-wide linkage scan in 63 extended families with multiple members with type II diabetes. Urinary albumin excretion, measured as the albumin-to-creatinine ratio (ACR), was determined in 426 diabetic and 431 nondiabetic relatives who were genotyped for 383 markers. The data were analyzed using variance components linkage analysis. Heritability (h2) of ACR was significant in diabetic (h2=0.23, P=0.0007), and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 40 publications
2
90
2
Order By: Relevance
“…Several regions of linkage have been replicated among the various groups with type 2 DN, as well. The 18q22-23 linkage region was replicated in four populations (23,26,29), the 7q35-36 peak in three reports (25,26,31), and the 7p15 and 10q26 peaks in two each (14,23,32). Positional candidate genes for DN in these regions are now being sought and identified (Table 2).…”
Section: Genome-wide Linkage Scans For Dnmentioning
confidence: 99%
“…Several regions of linkage have been replicated among the various groups with type 2 DN, as well. The 18q22-23 linkage region was replicated in four populations (23,26,29), the 7q35-36 peak in three reports (25,26,31), and the 7p15 and 10q26 peaks in two each (14,23,32). Positional candidate genes for DN in these regions are now being sought and identified (Table 2).…”
Section: Genome-wide Linkage Scans For Dnmentioning
confidence: 99%
“…The other study 56 investigated four different variants of eNOS than those described earlier: C1067T, A26G, G894T, and A15G; none of these variants produced a significant transmission (OR ϭ 1.15, 95% CI: 0.63-2.09, OR ϭ 1.08, 95% CI: 0.63-1.84, OR ϭ 1.10, 95% CI: 0.61-1.98, and OR ϭ 1.14, 95% CI: 0.64 -2.05, respectively). Only one genome-wide linkage scan 60 provided evidence of linkage at the chromosomal region 7q36, which harbors the eNOS gene. None of the genome-wide association studies 69,70 showed association with eNOS gene polymorphisms.…”
Section: Evidence From Family-based and Genome-wide Study Designsmentioning
confidence: 99%
“…These families belong to the Joslin Study on Genetics of Type 2 Diabetes -a collection of 104 extended families in which type 2 diabetes segregates as an autosomal dominant disorder. The ascertainment of these families and the recruitment procedures have been previously described [20]. The screening criteria were: 1) a proband and at least one sibling with type 2 diabetes diagnosed between ages 10 and 59 years; 2) three or more generations affected by diabetes; and 3) unilineal transmission of diabetes.…”
Section: Families With Type 2 Diabetesmentioning
confidence: 99%